2018
DOI: 10.3390/w10091237
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Equity and Inclusion in Access to Water and Sanitation for Persons Living with HIV/AIDS in Wukro, Ethiopia

Abstract: For more than a decade, foreign aid-supported water interventions focusing on an increase in household private connections have been implemented in the small urban center of Wukro. However, little has been investigated about the effectiveness of these interventions in achieving equitable and inclusive access to water and sanitation for all, including the most vulnerable. With this purpose, a cross-sectional comparative analysis of service provision between the HIV-infected population (n = 199) and non-infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The difference in the implementation period of the cited research works, agro-ecologic and cultural variations of the study areas might have contributed to the observed differences. The relatively lower burden of maternal undernutrition in the current study could partly be explained by the fact that the study area is known for being a hot-spot for various health and developmental interventions [ 53 55 ]. Nonetheless, the prevalence of maternal undernutrition is still high in our study community.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the implementation period of the cited research works, agro-ecologic and cultural variations of the study areas might have contributed to the observed differences. The relatively lower burden of maternal undernutrition in the current study could partly be explained by the fact that the study area is known for being a hot-spot for various health and developmental interventions [ 53 55 ]. Nonetheless, the prevalence of maternal undernutrition is still high in our study community.…”
Section: Discussionmentioning
confidence: 99%
“…As attested in the aforementioned literature, the important role of social dynamics and governance arrangements is well established. However, the continued, widespread inequities in water access across the globe despite investments in water resources developments, e.g., [29][30][31], suggest that these learnings have not consistently translated into improved water management. To address these persistent equity issues, Keeler et al [32] recently called for new approaches to collaboration and knowledge production in water management and policy that address some of the research blind spots, particularly around the justice dimensions.…”
Section: Equity Issues In Water Interventionsmentioning
confidence: 99%
“…Equity constitutes one of the three pillars of IWRM along with economic efficiency and environmental sustainability (GWP 2017). The social dimension of equity refers that the provision of water services is a basic right to all individuals and no one including poor and marginal people will be excluded from the services (GWP 2011;Jimenez-Redal et al 2018). The political dimensions include the distribution of power and wealth between different groups and individuals, and the processes that create, sustain and transform these relationships over time (Harris et al 2011).…”
Section: Re-conceptualising Iwrmmentioning
confidence: 99%